The controversial role of foreign fisheries consultants in Sierra Leone's coastal waters. (August 2020) - Okeke-Ogbuafor, Nwamaka; Gray, Tim; Stead, Selina Marguerite
Abstract: The use of foreign fisheries consultants in developing countries is increasing, despite growing controversy about their value. On the one hand, they bring expertise and analytic skills, which can turn around ailing fisheries, but on the other hand, their prescriptions may be inappropriate, based on ignorance or misunderstanding of local circumstances. This study, based on results from 51 key informant interviews and 199 survey questionnaires, finds the contributions of foreign fisheries consultants in Sierra Leone of limited benefit.